Ubiquitination of renal ENaC subunits in vivo - Frindt, Gustavo; Bertog, Marko; Korbmacher, Christoph; Palmer, Lawrence G. (American Journal of Physiology-Renal Physiology, 2020)
Ubiquitination of the epithelial Na+ channel (ENaC) in epithelial cells may influence trafficking and hormonal regulation of the channels. We assessed ENaC ubiquitination (ub-ENaC) in mouse and rat kidneys using affinity beads to capture ubiquitinated proteins from tissue homogenates and Western blot analysis with anti-ENaC antibodies. Ub-αENaC was observed primarily as a series of proteins of apparent molecular mass of 40-70 kDa, consistent with the addition of variable numbers of ubiquitin molecules primarily to the NH2-terminal cleaved fragment ( 30 kDa) of the subunit. No significant Ub-βENaC was detected, indicating that ubiquitination of this subunit is minimal. For γENaC, the protein eluted from the affinity beads had the same apparent molecular mass as the cleaved COOH-terminal fragment of the subunit ( 65 kDa). This suggests that the ubiquitinated NH2 terminus remains attached to the COOH-terminal moiety during isolation through disulfide bonds. Consistent with this, under nonreducing conditions, eluates contained material with increased molecular mass (90-150 kDa). In mice with a Liddle syndrome mutation (β566X) deleting a putative binding site for the ubiquitin ligase neural precursor cell expressed developmentally downregulated 4-2, the amount of ub-γENaC was reduced as expected. To assess aldosterone dependence of ubiquitination, we fed rats either control or low-Na+ diets for 7 days before kidney harvest. Na+ depletion increased the amounts of ub-αENaC and ub-γENaC by three- to fivefold, probably reflecting increased amounts of fully cleaved ENaC. We conclude that ubiquitination occurs after complete proteolytic processing of the subunits, contributing to retrieval and/or disposal of channels expressed at the cell surface. Diminished ubiquitination does not appear to be a major factor in aldosterone-dependent ENaC upregulation.
CRIS-Team Scopus Importer:2020-04-28
Keywords: epithelial Na+ channel; Liddle syndrome; mice; proteolysis; rats